Developing a framework for subcontractor appraisal using a balanced scorecard - Ng, S. Thomas; Skitmore, Martin (Journal of Civil Engineering and Management, 2014)
Subcontractors contribute significantly to construction projects and their performance can seriously affect over-all project success. It is crucial, therefore, to appraise the performance of subcontractors to ensure they satisfy the client’s expectations and project requirements. To increase the transparency and accuracy of subcontractor appraisal, the baseline and target performance levels should be set at the outset so that the appraisers and those being appraised realize exactly what standards are to be achieved. The balanced scorecard, being a powerful tool for performance appraisal, offers a potentially good approach for modeling the subcontractor appraisal process. In this paper, an approach to developing a balanced scorecard subcontractor appraisal model is proposed and demonstrated through a questionnaire survey administered in Hong Kong and from which the baseline and target performance levels for large-scale skilled subcontractors are identified. A case example is used to illustrate the operation of the model. Finally, a means by which the model may be validated is demonstrated through the use of field experts. The results demonstrate the feasibility of developing a balanced scorecard model that can help improve the transparency of subcontractor appraisal despite the baseline and target performance levels changing according to the project characteristics, subcontractor categories and size.